New Keynesian DSGE Models and the IS-LM Paradigm - Ulrich Frische; Ingrid Größl (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2010)
New Keynesian DSGE models propose a dynamic and expectational version of the old IS-LM paradigm. Acknowledging that the Taylor rule as a substitute for the LM-curve has its merits we show that standard DSGE models do not model how the central bank achieves its targets. In filling this gap we make evident that models neglecting a store-of-value function of money but still assuming a Taylor rule are inconsistent. Our major point concerns the-so called new Keynesian IS-curve. We prove that DSGE models which typically rest on the assumption of representative agents are unable to derive the IS-curve. This implies that these models lack the capability to analyse the role of savings as a a gap in aggregate demand. By assuming overlapping generations we make evident how this shortcoming can be avoided. We also show how OLG models add a richer dynamics to the standard DSGE approach.
urn:nbn:de:101:1-201101312792
Keywords: 330; Neukeynesianische Makroökonomik; Dynamisches Gleichgewicht; IS-LM-Modell; Overlapping Generations; Theorie